Left atrial appendage occlusion with the Amplatzer Cardiac Plug could improve survival and prevent thrombo-embolic and major bleeding events in atrial fibrillation patients with increased bleeding risk. Issue 2 (1st April 2016) - Budts, Werner; Laenens, Dorien; Calenbergh, Frank Van; Vermeersch, Paul; Potter, Tom De; Aminian, Adel; Benit, Edouard; Stammen, Francis; Kefer, Joelle
Abstract : Aims Literature suggests a beneficial effect of percutaneous left atrial appendage occlusion (LAAO) to prevent thrombo-embolic events in patients with non-rheumatic atrial fibrillation (AF). We compared outcome of LAAO versus 'suboptimal standard' treatment in AF patients with high bleeding risk. Methods and results Patients with sufficient follow-up data (n = 125) who underwent LAAO with the Amplatzer Cardiac Plug (ACP) were selected from the Belgian ACP database. AF patients who survived intracranial haemorrhage were recruited from the Leuven Neurosurgical Registry (LNR, n = 113). After propensity score adjustment, the outcome of both groups was compared for the combined end point (death, stroke, transient ischaemic attack, systemic emboli, and major bleeding event). The LAAO group did not differ from the LNR group for mean age and gender (74 ± 7 versus 75 ± 10 years, P = 0.29; female 39% versus 48%, P = 0.18). However, the CHA2DS2-VASc and HAS-BLED scores were both higher in the LAAO group (4.8 ± 1.7 versus 3.9 ± 1.7, P = 0.0001; 3.5 ± 1.4 versus 3.2 ± 1.4, P = 0.036). After propensity score adjustment, the risk for the primary end point was significantly higher for the LNR group (HR 2.012, 95% CI 1.113-3.638). Conclusion LAAO with ACP seems to improve the combination of survival and the prevention of thrombo-embolic and major bleeding events in patients with atrial fibrillation and increased bleeding risk.